Evaluación técnica y financiera a los diez pozos seleccionados para la inhibición de asfaltenos mediante aditivos químicos en el campo Río ceibas de la cuenca del valle superior del Magdalena (2017)
This research seeks in a direct way to rescue wells candidates to be the pilots in the Río Ceibas Field from a list of wells all affected by the precipitation of asphaltenes, perhaps it is one of the few things that these wells have in common their asphaltene damage , As far as the other characteristics are very different and from there the function of this work of gathering the information to study it to handle it and use it to give priority to the wells that could be more appropriate to be injection pilots Huff & Puff in the future.